Investigation of conventional and ultrasonic vibration-assisted turning of hardened steel using a coated carbide tool - Ghule, Govind S.; Sanap, Sudarshan; Chinchanikar, Satish; Cep, Robert; Kumar, Ajay; Bhave, Suresh Y.; Kumar, Rakesh; Altarazi, Faisal (Frontiers in Mechanical Engineering, 2024)
This study compares conventional turning (CT) and ultrasonic vibration-assisted turning (UVAT) in machining hardened AISI 52100 steel (62 HRC) with a PVD-coated TiAlSiN carbide tool. UVAT experiments, utilizing a 20 kHz ultrasonic frequency and 20 µm vibration amplitude, varied cutting speed, feed, and depth of cut. Remarkably, UVAT reduced tool wear, extending tool longevity. Surprisingly, power consumption showed no significant differences between CT and UVAT. Mathematical models based on experimental data highlight cutting speed's substantial impact on tool wear, with depth of cut closely following. For power consumption, the depth of cut took precedence, with cutting speed and feed rate playing pronounced roles in UVAT. This emphasizes the potential for further research into machinability, particularly exploring different vibration directions on the tool in feed, tangential, and radial aspects.